Treatment of older patients with multiple sclerosis: Results of an International Delphi Survey - Tumani, Hayrettin; Coyle, Patricia K; Cárcamo, Claudia; Cordioli, Cinzia; López, Pablo A; Peterka, Marek; Ramo-Tello, Cristina; Zuluaga, María I; Koster, Thijs; Vignos, Megan (Multiple sclerosis journal - experimental, translational and clinical, 2023)
BACKGROUND: People over age 50-55 have historically been excluded from randomized clinical trials for multiple sclerosis (MS). However, more than half of those living with an MS diagnosis are over 55. OBJECTIVE: Explore the unique considerations of treating older people with MS (PwMS) using an iterative and structured Delphi-based assessment to gather expert opinions. METHODS: Eight MS neurologists with an interest in older PwMS developed a 2-round survey. Survey respondents were qualified neurologists with ≥3 years' experience, personally responsible for treatment decisions, and treating ≥20 patients per month, of whom ≥10% were ≥50 years old. Consensus was defined as ≥75% agreement on questions with categorical responses or as a mean score ≥4 on questions with numerical responses. RESULTS: In Survey 1, 224 neurologists responded; 180 of these completed Survey 2. Limited consensus was reached with varying levels of agreement on several topics including identification and assessment of older patients; factors relating to treatment decisions including immunosenescence and comorbidities; considerations for high-efficacy treatments; de-escalation or discontinuation of treatment; effects of COVID-19; and unmet needs for treating this population. CONCLUSION: The results of this Delphi process highlight the need for targeted studies to create guidance for the care of older PwMS.
Keywords: older patients; Delphi technique; treatment recommendations; Multiple sclerosis; standards; consensus